Earnings management in private firms: An empirical analysis of determinants and consequences of earnings management in private firms - Morten Nicklas Bigler Jensen (Copenhagen Business School (CBS), 2019)
This dissertation seeks to understand the determinants and implications of earnings management in private firms, an economically significant yet not well researched segment of the economy. Earnings management occurs when a firm uses discretion and judgement in financial reporting to alter financial reports to mislead stakeholders or to influence contractual outcomes that depend on the reported numbers, and inherently impair the quality of financial reports, and thus hinders efficient capital allocation. The dissertation consists of three chapters that are written in the form of separate academic research papers that can be read independently of each other. Despite the chapters being separate academic research papers, all three chapters are related as they all investigate earnings management in private firms, however from different angles and at different levels of analysis. The first chapter explores on a firm level how financially distressed firms use financial reporting when they face financial distress, and find that they use discretion in the accrual estimation process to signal private information and resolve information asymmetries. The second chapter focuses on earnings management driven by the firm's CEO and exploits a setting in which an owner-manager at own discretion can shift her income from salary to dividends at almost no direct cost and hence increase reported earnings. Then, the paper explores determinants and cost of debt implications of this type of income shifting in owner-managed firms, and finds that such behavior is related to the level of debt, and has implications in the form of lower cost of debt. The third and last chapter moves beyond the firms' executives and explores if rank-and-file employees explain variation in financial reporting, and find that they do. Specifically, I find that firms with a large percentage of criminal employees are more likely to engage in earnings management. The following section briefly summarizes each of the three papers by their abstracts.
hdl:10398/9774
Keywords: 650; Bilanzpolitik; Privatwirtschaft; Welt